The Influence of Financial Literacy and Financial Inclusion on The Sustainability of Traders' Businesses in Pasar Baru Arengka Pekanbaru - Friska Dian Kristy Simanjuntak; ruzikna (Institute of Computer Science (IOCS), 2024)
The increasingly competitive business world requires strategies to win the competition. A business that is able to survive for a long time proves that the business can maintain business continuity. This research aims to determine and analyze the influence of financial literacy and financial inclusion on the sustainability of traders' businesses at Pasar Baru Arengka Pekanbaru. The research method used is quantitative. The research sample was 73 respondents using proportionate stratified random sampling technique. The data collection technique uses a questionnaire which is processed with parametric inferential statistics using SPSS 22. The research results obtained are that the higher level of financial literacy will also the higher the level of business sustainability, the higher level of financial inclusion will also the higher level of business sustainability, and the higher level of financial literacy and financial inclusion will also the higher the level of business sustainability of traders in Pasar Baru Arengka Pekanbaru